Rediscovery of Ixodes confusus in Australia with the first description of the male from Australia, a redescription of the female and the mitochondrial (mt) genomes of five species of Ixodes. (August 2022) - Barker, Dayana; Kelava, Samuel; Seeman, Owen D.; Shao, Renfu; Seaniger, James R.; Jones, Malcolm K.; Apanaskevich, Maria A.; Nakao, Ryo; Apanaskevich, Dmitry A.; Barker, Stephen C.
Abstract: We: (i) report the rediscovery of Ixodes ( Sternalixodes ) confusus Roberts, 1960 in Australia; (ii) redescribe the male and female of I. confusus ; (iii) describe the mitochondrial (mt) genome of I . confusus from five ticks from four localities in Far North Queensland; and (iv) present the first substantial phylogeny of the subgenera of the Ixodes . The mt genomes of I. confusus, I. cornuatus, I. hirsti, I. myrmecobii and I. trichosuri are presented here for the first time . In our phylogeny from entire mt genomes (ca. 15 kb), the subgenus Endopalpiger was the sister-group to subgenera Sternalixodes plus Ceratixodes plus Exopalpiger whereas Exopalpiger was the sister to Sternalixodes plus Ceratixodes . [i.e. (( Endopalpiger ) ( Sternalixodes, Ceratixodes and Exopalpiger ))]. Finally, we show that Ixodes anatis, the kiwi tick, may be closely related to the ticks of marsupials of Australia and Papua New Guinea . Graphical abstract: Image 1 Highlights: Rediscovery in Australia of the tick, Ixodes confusus. First description of the male of Ixodes confusus from Australia. Nine new mitochondrial genomes of Ixodes ticks from Australia and first substantial phylogeny of the subgenera of Ixodes. Ixodes anatis, a tick of the kiwi bird of NZ may be a closely related to the ticks of marsupials of Australia and PNG.